The Effectiveness of Psychoeducation in Increasing Adolescents’ Knowledge of the Risks of Premarital Sexual Behavior among 11th Grade Students at X Senior High School - Aditya Briliant Ananta; Dea Fenny Kirana Putri; Novilia Berliani; Nabiella Annaejla; Aidil Rizki; Prima Aulia (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
Premarital sexual behavior among adolescents has become an increasing concern in the digital era, given its potential health and psychosocial risks. The lack of comprehensive sexual education in schools often results in adolescents obtaining misleading information from media or peers. This study aimed to examine the effectiveness of psychoeducationin enhancing the knowledge of 11th-grade students at X Senior High School regarding the risks of premarital sexual behavior. A quasi-experimental design with pretest and posttest was employed, involving 20 purposively selected students. The psychoeducational intervention consisted of two face-to-face sessions utilizing lectures, group discussions, educational videos, and role-play. The level of knowledge was measured using a validated premarital sexual behavior scale. The results indicated a significant improvement in students’ knowledge (t(19) = 7.027; p < 0.001), with a large effect size (Cohen’s d = 1.571). The negative correlation between pretest and posttest scores suggested that students with lower initial knowledge experienced greater improvement. These findings support that psychoeducation is an effective method for enhancing adolescents’ understanding of sexual risks. Further research is recommended to be conducted with a more diverse population and to consider external factors such as family influence and media exposure.